Potential Effects of Omega-3 Fatty Acids on Type 1 Diabetes in Preventing Alzheimer’s Disease Progression - Titisari, Nurina; Ahmad, Hafandi; Fauzi, Ahmad; Samsulrizal, Nurdiana; Razak, Intan Shameha Abdul (Universitas Airlangga, 2025)
The human metabolic syndrome of diabetes is widely reported globally. People with type 1 diabetes (T1D) are at high risk for developing diabetic complications. Increasing evidence in clinical studies and literature reviews suggests that T1D has a strong relation with cognitive impairments, leading to a higher occurrence of dementia and Alzheimer’s disease (AD). Research has shown that diet has a significant impact that may delay the onset of diabetes problems. Recent findings have demonstrated that omega-3 fatty acids act as a neuroprotective agent against the development of brain disorders. However, the positive impact of omega-3 fatty acids against diabetes, particularly on T1D, has debatable roles due to data inconsistencies. This review will discuss the mechanism of T1D on AD and the potential role of omega-3 fatty acids in degrading AD risk in patients with T1D. Scientific reports from epidemiological, molecular, and animal models and human studies are highlighted in this study. In conclusion, despite the conflicting results observed in both experimental and clinical studies, omega-3 fatty acids were proven to exhibit anti-inflammatory characteristics and alleviate autoimmune activities. Hence, omega-3 fatty acids are suggested to be considered in the prevention of AD progression, particularly in T1D patients. Nevertheless, the role of omega-3 fatty acids supplementation in T1D patients needs further exploration.